Analysis of Total Oil Concentration and Phythoplankton Community Structure in the Waters of Pelintung Industrial Area - Nurrachmi, Irvina; Nedi, Syahril; Khaironisa, Riska (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research was conducted in July 2020 in Pelintung Dumai Waters. The purpose of this study was to determine the relationship between total oil concentration and the abundance of phytoplankton. The method used is a survey method which is conducted at 4 stations. Based on the results of the study, the highest oil concentration was in the waters of the Pelintung industrial area (station III), namely 0.3245 ppm and the lowest concentration was in the mangrove forest area (station IV), namely 0.0738 ppm. There are 21 species of phytoplankton found in Pelintung waters. The highest abundance was found in the tourist area (station I) which was 166 ind / l and the lowest abundance was found in the mangrove forest area (station IV) which was 138 ind / l. The relationship between total oil concentration and phytoplankton abundance is negative, which means that every time there is an increase in total oil concentration, there is a decrease in the abundance of phytoplankton in Pelintung waters